Bilateral tonic seizures probably induced by eperisone hydrochloride: a case report - Luo, Long; Yin, Jun; Li, Zhigang; Zhang, Wei; Yuan, Ying; Tang, Ying; Deng, Ye; Zhu, Ling (Frontiers in Neurology, 2023)
Eperisone hydrochloride is a central muscle relaxant used to treat osteoporosis. Seizures are rare side effects of eperisone hydrochloride, which have been previously reported in overdose situations but have not been reported at regular doses in the medical literature. This case report describes a 42-year-old male painter who developed severe bilateral tonic seizures after the initiation of eperisone hydrochloride at regular doses for low back pain. Symptoms gradually eased in the days following the discontinuation of eperisone hydrochloride and antiepileptic treatment, with no recurrence. This rare adverse drug reaction warrants clinical awareness; however, the mechanisms underlying these adverse reactions remain to be clarified.